Wind environment evaluation in neighborhood residential areas in Malaysia:a case study of Johor Bahru metropolitan city - Tetsu, Kubota; Ahmad, Supian (2004)

(untitled)
This paper discusses planning guidelines at the neighborhood residential areas in consideration of wind flow in Malaysia. It aims to reduce the energy consumption particularly from the usage of home air conditioners. Natural wind flow is one of the most effective methods to help achieve the energy saving objectives in large cities especially under the tropical climate like Malaysia. This paper presents the results of several wind tunnel tests on selected neighborhood residential areas in the Johor Bahru Metropolitan City. Moreover, the wind environment evaluation of the selected case study areas under the climate conditions of the city was carried out. The results of the evaluation shows that the mean wind velocities at 1.5m height of some of the Malaysian terraced houses cases were in the comfort zone particularly during the northeast monsoon period. Nevertheless, both in the southwest monsoon period and the inter monsoon period, although the mean values of wind velocity ratio of the Malaysian terrace houses had been slightly higher than the trend line of the Japanese apartment houses, the mean wind velocities in all the cases in the Johor Bahru City and Japan did not reach the required comfort zones.